Factors Associated with Unmet Need for Healthcare Among Older Adults in Thailand - Meemon, Natthani (Animo Repository, 2019)
Although Thailand’s Universal Coverage Scheme (UCS) has provided almost free healthcare access, there is still a concern of unmet healthcare need especially for older adults due to their mobility limitations. Thus, this study investigated factors associated with unmet healthcare need among older adults under the UCS context. Descriptive and binomial logistic regression analyses with the nationwide Health and Welfare Survey 2015 data were performed to explore socioeconomic characteristics of older adults, and investigate whether the socioeconomic characteristics were associated with unmet healthcare need. The results indicated that mobility limitation was a major reason for the unmet need. Additionally, long wait-time in and long distance to healthcare facilities were significantly associated with the unmet need. For socioeconomic conditions, older adults, as compared to younger ones, generally had low income and education levels, were unemployed and chronically ill, and lived without a spouse. Such socioeconomic conditions were even worse for the older adults who experienced the unmet need than those who did not. By the results, policy interventions must set priorities of older adults according to their vulnerability. Specifically, older adults who have a mobility limitation and live alone without a regular connection or support must be the first target group. In the short term, the current village health volunteer program should assist the urgent needs of older adults through home care and emergency van arrangement services. In the long-term, the government should continue the investments for the current limited healthcare resources through the National Health Development Plan.